1995
DOI: 10.1007/bf00166608
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctiva and subconjunctival tissue in primary open-angle glaucoma after long-term topical treatment: an immunohistochemical and ultrastructural study

Abstract: According to these results, antiglaucomatous surgery should be rehabilitated and considered as an alternative to long-term medical therapy in the first-instance treatment of primary open-angle glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
2
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 20 publications
1
52
2
2
Order By: Relevance
“…Long-time usage of antiglaucomatous agents was shown to cause irreversible chronic conjunctival inflammation and fibrosis which yields a low success rate in filtration surgery [4,5,6,7,11,12,13,14,38,39,40]. It was shown that the changes were more prominent in patients treated with more than one drug and with increased duration of time [7, 11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-time usage of antiglaucomatous agents was shown to cause irreversible chronic conjunctival inflammation and fibrosis which yields a low success rate in filtration surgery [4,5,6,7,11,12,13,14,38,39,40]. It was shown that the changes were more prominent in patients treated with more than one drug and with increased duration of time [7, 11].…”
Section: Discussionmentioning
confidence: 99%
“…The conjunctiva is a living tissue and can respond to topical medication with inflammation, scarring, keratinization and neovascularization [2,3,4,5,6,7]. Topical medications may also have an adverse effect on the tear film and on mucus production [3, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Ис-пользование даже одного вида капель в течение трёх лет и более также ассоциировано с разви-тием воспаления и инфильтрацией фибробласта- ми, что напрямую коррелирует с повышенным риском неэффективности хирургического вмеша-тельства [22]. Обследуя пациентов, находящихся на длительной местной терапии, R. Nuzzi (1995) подтвердил факт существенного утолщения слоёв эпителиальных клеток, увеличения численности фибробластов в субэпителиальном и глубоком со-единительнотканном слое и уплотнение соедини-тельной ткани, в которой возрастает содержание коллагеновых волокон, упорядоченных в виде за-витков, и усиливается экспрессия маркеров вос-паления [33]. По данным C. Baudouin (1999), ре-зультаты иммуногистологических исследований образцов конъюнктивы и трабекулы пациентов, готовящихся к антиглаукомной операции, свиде-тельствуют о том, что на фоне медикаментозной терапии имеет место более выраженная экспрес-сия маркеров активации фибробластов и мар-керов воспаления, чем в его отсутствие.…”
Section: The Influence Of Local Iop-lowering Therapy On the Anterior unclassified
“…Результаты других исследований позволяют выдвинуть гипотезу о том, что местная терапия, возможно, по причине содержания консервантов может играть определённую роль в созревании катаракты [33], а также в увеличении частоты встречаемости кистозного макулярного отёка, диагностируемого по результатам ангиографии, после оперативного вмешательства по поводу ка-таракты [17]. Гибель клеток и выработка сигналов каскада воспаления, имеющие место в подлежа-щих структурах (тенонова капсула, субконъюн-ктивальное пространство и даже трабекулярная сеть), могут принимать непосредственное уча-стие в индукции послеоперационного воспаления и фиброза и обусловливать последующее повы-шение внутриглазного давления.…”
Section: The Influence Of Local Iop-lowering Therapy On the Anterior unclassified
“…But although most of the studies report conjunctival inflammation in prostaglandin analogues users 7,8,10,12 , this feature may also be present in patients under the use of other antiglaucomatous drugs 9,10,[13][14][15] .…”
Section: Introductionmentioning
confidence: 99%